Child's challenging behaviour scale, version 2 (CCBS-2): Psychometric evaluation with young children - Bourke-Taylor, H.; Pallant, J.; Cordier, Reinie (American Occupational Therapy Association, Inc., 2017)
OBJECTIVE: In this article, we evaluate psychometric properties of the Child's Challenging Behaviour Scale, Version 2 (CCBS-2) with mothers of young, typically developing children. METHOD: A cross-sectional mail survey with Australian mothers (N = 337) included the CCBS-2, the Depression Anxiety Stress Scales, and the Parents' Evaluation of Developmental Status scale. RESULTS: Internal consistency was good, and no gender differences in CCBS-2 scores were significant. Significant results included differences between CCBS-2 scores: among children grouped according to age, among children grouped according to pre- and post-school entry, among mothers grouped according to extent of any symptom type, and between this sample and a previously collected age-matched sample of children with disabilities. CONCLUSION: Of the properties tested, results support sound psychometrics. The CCBS-2 can be used to differentiate children according to age, school entry, and disability as well as to identify families for potential services in behavior management and mental health.